2020
DOI: 10.1108/ics-11-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

An activity theory approach to information security non-compliance

Abstract: Purpose The purpose of this paper is to introduce activity theory (AT) as a new theoretical lens to the field of information security non-compliance by explaining how research in that field can benefit from AT and to suggest eight propositions for future research. Design/methodology/approach Based on AT, the paper suggests that employees, IT systems, task characteristics, information security policies (ISPs), community and division of labor can be viewed to form an ensemble that is labeled activity. Their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The organizational role embodies the responsibilities, duties, and functions assigned to individuals within the organizational structure Khatib and Barki (2020). It serves as a framework that delineates the scope of an individual's professional engagement and the tasks they are expected to perform.…”
Section: Hypotheses Discussionmentioning
confidence: 99%
“…The organizational role embodies the responsibilities, duties, and functions assigned to individuals within the organizational structure Khatib and Barki (2020). It serves as a framework that delineates the scope of an individual's professional engagement and the tasks they are expected to perform.…”
Section: Hypotheses Discussionmentioning
confidence: 99%
“…However, as Sommestad et al (2014) observed in their meta-analysis, the results of the 29 studies they examined have not been consistently similar, with variables showing considerable variations among different studies in terms of how they influenced compliant/ non-compliant behaviors. Recent studies have also suggested that an interplay is likely to exist among the variables that explain non-compliance (Khatib and Barki, 2020b;Vance et al, 2020;Woltjer, 2017). This paper draws from RCT to explain the different possibilities summarized above.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Despite the growing literature on information security non-compliance, recent research has observed disparate results among the variables that have been used to explain noncompliance (Sommestad et al, 2014). This, in turn, suggests that examining an interplay of variables could better explain non-compliance (Khatib and Barki, 2020b;Woltjer, 2017). This paper drew from rational choice theory (RCT) to follow these suggestions and examine what motivates many employees to engage in non-compliant behaviors routinely.…”
mentioning
confidence: 99%
“…There has been little research attention paid to the role of organizational factors in relation to the management of information security (Al-Darwish and Choe, 2019). Khatib and Barki (2020) held forth that it is important to consider the organizational circumstances, not only individual perceptions, when trying to understand non-compliance in information technology (IT) contexts. Factors, such as organizational security culture and climate, and sanctions (Alfawaz et al, 2010;Bulgurcu et al, 2010;D'Arcy et al, 2014), have been found to influence information security compliance.…”
Section: Introductionmentioning
confidence: 99%